DEVELOPMENT OF KNOWLEDGE ON PROFESSIONAL EDUCATION AT A SPECIALIZED SCHOOL (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the article, the professional competence of pedagogic personnel of specialized school students in order to regularly update professional knowledge, skills and qualifications in development, to improve pedagogical mechanisms and the quality of professional education the conducted researches are recorded. From the scientific and pedagogical potential of teaching staff based on satisfying their professional needs, education, science and production the quality of training of pedagogic personnel by ensuring its integration Opinions on increasing qualification requirements were expressed.